The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1111/j.1467-9221.2010.00819.x
|View full text |Cite
|
Sign up to set email alerts
|

It's My Campaign I'll Cry if I Want to: How and When Campaigns Use Emotional Appeals

Abstract: Recent research in the arena of campaign advertising suggests that emotional appeals can influence political attitudes, electoral choices and decision-making processes (Brader 2006;Marcus, Neuman and MacKuen 2000; Redlawsk, Civettini and Lau 2007). Yet is there any evidence that candidates use emotional appeals strategically during campaigns? Is there a pattern to their use? For instance, are fear appeals used primarily late in the campaign by trailing candidates in order to get voters to rethink their choices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
83
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(91 citation statements)
references
References 32 publications
7
83
0
1
Order By: Relevance
“…The moderating role of a priori attitudes found in Experiment 2 suggests as much. Corroborating evidence comes from an experimental study that found a strong effect of an anger‐inducement manipulation on a measure of political participation (Valentino et al, , Study 1, see also Marcus et al, ; Ridout & Searles, ). However, the present results suggest that expressing anger can be a double‐edged sword.…”
Section: Methodsmentioning
confidence: 99%
“…The moderating role of a priori attitudes found in Experiment 2 suggests as much. Corroborating evidence comes from an experimental study that found a strong effect of an anger‐inducement manipulation on a measure of political participation (Valentino et al, , Study 1, see also Marcus et al, ; Ridout & Searles, ). However, the present results suggest that expressing anger can be a double‐edged sword.…”
Section: Methodsmentioning
confidence: 99%
“…With this in mind, are the candidates’ personality profiles associated with their use of negativity and emotionality? Research on the strategic reasons for competing candidates to go negative (and emotional) is widespread (e.g., Nai and Walter ; Ridout and Searles ), but virtually nothing is known about whether campaigning is also driven by the personality of candidates. And yet, good reasons exist that it should, as growing evidence suggests that personality and communication behavior are strongly associated (de Vries et al ).…”
Section: Empirical Evidencementioning
confidence: 99%
“…On the one hand, if the electoral effectiveness of negative campaigning techniques is still contested (Lau, Sigelman, and Rovner 2007), mounting evidence seems to suggest that negativity is associated with unintentional systemic effects, for instance, depressed turnout and mobilization (Ansolabehere and Iyengar 1995) or increased cynicism, apathy, and a gloomier public mood (Yoon, Pinkleton, and Ko 2005). On the other hand, the use of emotional elements in campaigning (Brader 2006;Ridout and Searles 2011) starts from the assumption that feelings and emotions act as powerful determinants of attitudinal behavior (Marcus and MacKuen 1993;Marcus, Neuman, and MacKuen 2000): anxious citizens are likely to pay more attention to information and campaigns, which makes them easier targets for persuasion (Nai, Schemeil, and Marie 2017); enthusiastic citizens are more likely to get invested and participate (Marcus and MacKuen, 1993), but they do so by relying strongly on their previously held partisan beliefs and attitudes (Marcus, Neuman, and MacKuen 2000).…”
Section: The Studymentioning
confidence: 99%
“…Another reason that I focus on positive emotions is that parties engage in more positive campaigning than negative campaigning to target copartisan voters. Studies in the United States show that positive ads are more effective than negative ads for mobilization (Brader ) and that parties use enthusiastic appeals to mobilize the base (Ridout and Searles ). In addition, on page 9 of the supporting information (SI), I show that the campaign texts I analyze in the empirical section contain only a few negative moral appeals.…”
mentioning
confidence: 99%